Usefulness of protein-based salivary markers in the diagnosis of oral potentially malignant disorders: A systematic review and meta-analysis - Arroyo, Esteban [UNESP]; Donís, Sergio Piñeiro [UNESP]; Petronacci, Cintia M. Chamorro; Alves, Monica G. Oliveira; Mendía, Xabier Marichalar; Fernandes, Darcy [UNESP]; Pouso, Alejandro I. Lorenzo; Bufalino, Andreia [UNESP]; Bravo López, Susana; Sayáns, Mario Pérez [UNESP] (SAGE Publications, 2021)
By using a meta-analytical approach, this study aimed to analyse the diagnostic capacity of protein-based biomarkers in saliva for the differential diagnosis of oral potentially malignant disorders (OPMDs) and oral squamous cell carcinoma (OSCC) from healthy individuals as control group (HCG). Articles on protein-based biomarkers in saliva, which provided quantitative expression in individuals with clinical and histopathological diagnosis of OPMD or oral leukoplakia (OL) were considered eligible. Searches were conducted in eight electronic databases. The methodological quality was assessed using the Quality Assessment of Diagnostic Studies tool (QUADAS-2). Functional analysis was also performed. Meta-analyses were performed using the OpenMeta tool (Analyst). Meta-analysis was possible for 4 of the 11 biomarkers studied. Only the carcinoembryonic antigen (CEA) and the soluble fragment of cytokeratin 19 (CYFRA21) were significant for the OSCC/OPMD subgroup, both with a very low heterogeneity. CEA had an OE = 25.854 (CI95%: 13.215-38.492, p< 0.001, I2 = 0) and CYFRA21 had an OE = 9.317 (CI95%: 9.014-9.619, p< 0.001, I2 = 0). For the OPMD/HCG subgroup, only CYFRA21 was significant, with an OE = 3.679 (CI95%: 0.663-6.696, p= 0.017) although with high heterogeneity (I2 = 91.24). The CEA and CYFRA21 markers proved very useful when differentiating OSCC from OPMD. The CYFRA21 was the only protein that was capable of distinguishing between OPMD and healthy controls.
Keywords: meta-analysis; oral leukoplakia; oral potentially malignant lesions; protein-based biomarkers; saliva; Systematic review